Quantitative Analysis of Road Transport Agreements (QuARTA) - Kunaka, Charles; Tanase, Virginia; Latrille, Pierre; Krausz, Peter (Washington, DC: World Bank, 2013)
Road freight transport is indispensable to international economic cooperation and foreign trade. Across all continents, it is commonly used for short and medium distances and in long distance haulage when minimizing time is important. In all instances governments play a critical role in ensuring the competitive advantage of private sector operators. Countries often have many opportunities to minimize the physical or administrative barriers that increase costs, take measures to enhance the attractiveness and competitiveness of road transport, or generally nurture the integral role of international road freight transport in the global trade logistics industry. Road freight transport is critical to domestic and international trade. It is the dominant mode of transport for overland movement of trade traffic, carrying more than 80 percent of traffic in most regions. Generally, nearly all trade traffic is carried by road at some point. Therefore, the cost and quality of road transport services is of critical importance to trade competitiveness of countries and regions within countries. In fact, road transport is fundamental to modern international division of labor and supply-chain management.